2021
DOI: 10.1021/acsomega.1c05024
|View full text |Cite
|
Sign up to set email alerts
|

Micromixer with Fine-Tuned Mathematical Spiral Structures

Abstract: Micromixers with the microchannel structure can enable rapid and efficient mixing of multiple types of fluids on a microfluidic chip. Herein, we report the mixing performance of three passive micromixers based on the different mathematical spiral structures. We study the fluid flow characteristics of Archimedes spiral, Fermat spiral, and hyperbolic spiral structures with various channel widths and Reynolds number (Re) ranging from 0 to 10 via numerical simulation and visualization experiments. In addition, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Therefore, the fluid with Re of 5 is chosen for the experiment in order to ensure the homogeneous mixing of the sample during the experiment. 36…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the fluid with Re of 5 is chosen for the experiment in order to ensure the homogeneous mixing of the sample during the experiment. 36…”
Section: Resultsmentioning
confidence: 99%
“…When M = 0 indicated that the fluid was not mixed, M = 1 indicated that the liquid was completely mixed. 39 where c m̄ is mass fraction of the concentration of the liquid when it was completely mixed and c i the mass fraction of the concentration at each equal division.…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, the smaller volume significantly reduces reagent consumption and greatly saves costs. High integration of different functions in a small space is also suitable for POCT development requirements [26]. On the other hand, the large surface-volume ratio allows diffusion and heat conduction to be efficient [27,28].…”
Section: Rt-pcr Testsmentioning
confidence: 99%